REDD+, Community Forestry & Gender: Lessons Learned and Paths Forward - Rodgers, Mélissa (Université d'Ottawa | University of Ottawa, 2012)
Proposals for Reducing Emissions from Deforestation and Forest Degradation (REDD+) that are gaining prominence in international climate change negotiations offer both risks and opportunities for members of forest-dependent communities in developing countries. The livelihoods of rural women are often particularly dependent on forest resources, and yet REDD+ appears to be developing as a gender-blind institution. In this paper, I argue that REDD+ should be framed as an international development initiative. Following Amartya Sen’s capabilities approach, this requires that all members of forest-dependent communities be provided with opportunities to substantively participate in REDD+ programs. Community forestry programs offer a valuable precedent for REDD+. Drawing on Nepal’s extensive experience with community forestry, this paper explores the barriers to women’s participation in forest governance and possible strategies to overcome them, and examines gender equity in Nepal’s REDD+ preparedness activities to date.